Safety and Dosing Study of Glucagon‐Like Peptide 2 in Children With Intestinal Failure. (15th October 2015) - Sigalet, David L.; Brindle, Mary; Boctor, Dana; Casey, Linda; Dicken, Bryan; Butterworth, Sonia; Lam, Viona; Karnik, Vikram; de Heuvel, Elaine; Hartmann, Bolette; Holst, Jens
Abstract : Background and Aims: A glucagon‐like peptide 2 (GLP‐2) analogue is approved for adults with intestinal failure, but no studies of GLP‐2 have included children. This study examined the pharmacokinetics, safety, and nutritional effects of GLP‐2 in children with intestinal failure. Methods: Native human GLP‐2(1‐33) was synthesized following good manufacturing practices. In an open‐label trial, with parental consent, 7 parenteral nutrition–dependent pediatric patients were treated with subcutaneous GLP‐2 (20 µg/kg/d) for 3 days (phase 1) and, if tolerated, continued for 42 days (phase 2). Nutritional treatment was directed by the primary caregivers. Patients were followed to 1 year. Results: Seven patients were enrolled (age: 4.0 ± 0.8 years; bowel length, mean ± SEM: 24% ± 4% of predicted). All were parenteral nutrition dependent since birth, receiving 44% ± 5% of calories by parenteral nutrition. GLP‐2 treatment had no effect on vital signs (blood pressure, heart rate, and temperature) and caused no significant adverse events. Peak GLP‐2 levels were 380 pM (day 3) and 295 pM (day 42), with no change in half‐life or endogenous GLP‐2 levels. Nutritional indices showed a numeric improvement in z scores and citrulline levels; the z score was maintained while citrulline levels returned to baseline once GLP‐2 was discontinued. Conclusions: GLP‐2 was well tolerated in children, with a pharmacokinetic profile similar to that of adults. There were no changes in endogenous GLP‐2 release or metabolism. These results suggest that GLP‐2 ligands may be safely used in pediatric patients; larger trials are suggested to investigate nutritional effects.